Ablation of Dual-Specificity Phosphatase 6 Protects against Nonalcoholic Fatty Liver Disease via Cytochrome P450 4A and Mitogen-Activated Protein Kinase - Jiang, Can; Saiki, Yuriko; Hirota, Shuto; Iwata, Kosei; Wang, Xinyue; Ito, Yutaka; Murakami, Keigo; Imura, Takehiro; Inoue, Jun; Masamune, Atsushi; Hirayama, Akiyoshi; Goto, Masafumi; et al. (The American journal of pathology, 2023)
Dual-specificity phosphatase 6 (DUSP6) is a specific phosphatase for mitogen-activated protein kinase (MAPK). This study used a high-fat diet (HFD)–induced murine nonalcoholic fatty liver disease model to investigate the role of DUSP6 in this disease. Wild-type (WT) and Dusp6-haploinsufficiency mice developed severe obesity and liver pathology consistent with nonalcoholic fatty liver disease when exposed to HFD. In contrast, Dusp6-knockout (KO) mice completely eliminated these phenotypes. Furthermore, primary hepatocytes isolated from WT mice exposed to palmitic and oleic acids exhibited abundant intracellular lipid accumulation, whereas hepatocytes from Dusp6-KO mice showed minimal lipid accumulation. Transcriptome analysis revealed significant down-regulation of genes encoding cytochrome P450 4A (CYP4A), known to promote ω-hydroxylation of fatty acids and hepatic steatosis, in Dusp6-KO hepatocytes compared with that in WT hepatocytes. Diminished CYP4A expression was observed in the liver of Dusp6-KO mice compared with WT and Dusp6-haploinsufficiency mice. Knockdown of DUSP6 in HepG2, a human liver-lineage cell line, also promoted a reduction of lipid accumulation, down-regulation of CYP4A, and up-regulation of phosphorylated/activated MAPK. Furthermore, inhibition of MAPK activity promoted lipid accumulation in DUSP6-knockdown HepG2 cells without affecting CYP4A expression, indicating that CYP4A expression is independent of MAPK activation. These findings highlight the significant role of DUSP6 in HFD-induced steatohepatitis through two distinct pathways involving CYP4A and MAPK.